Penal enlightenment in Spain: From Beccaria's reception to the first criminal code - Aguero, Alejandro (2012)
It is almost a commonplace to say that since Beccarias's "On crimes and punishment" was translated and spread throughout Europe, it became a tipping point in the history of penal thinking and legal reforms. In Spain, some scholars have even classified the penal thinking of that time in “pre Beccaria” and “post Beccaria Spanish Enlightenment”. Being so, and looking at the history of criminal justice in Spain at the ending of the 18th century and beginning of the 19th, one may ask why did Spanish jurists fail to achieve an institutional change in such a substantive matter during that period? A complete answer to this question would require a deeper and longer analysis: the problematic relationship between Catholicism and the Enlightenment and the deterrent that the experience of the French revolution meant for the Spanish reformist, should be taken into account. However, our purpose in this essay is limited to showing why the Spanish legal doctrine was not able to assume all of the consequences implied in enlightened penal thinking as was exposed in Beccaria's "On crime and punishments". Considering its circulation in Spain, we would proceed to identify certain discursive keys that conditioned its reading and its general acceptance among Spanish publicists and jurists of this time.